El estudio del capital intelectual en la Universidad Tecnológica de la Construcción, en la ciudad de Morelia, Michoacán - González Ruiz, María Guadalupe (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
This thesis research paper addresses Intellectual Capital as part of the intangible assets held by people working in companies and gaining relevance to give it an economic value. Universities, like any organization in conjunction with their collaborators, acquire and generate knowledge day by day, as technological and scientific changes are constantly presented, as well as new procedures, among others. The changes are so constant that companies must be prepared to receive them, systematize them, apply them and renew them. However, it is the intellectual capital that is responsible for identifying, registering, systematizing and applying them. The application of the Euroforum Intelect Model is carried out at the Technological University of Construction, in the City of Morelia, Michoacán. Through which fundamental quantitative and qualitative variables are approached in this construct, facilitating evaluation of the Intellectual Capital of the teaching staff. Seeking as sole purpose to optimize resources as an integral part of a strategy that generates competitive advantages in the organization. For the data collection, the questionnaire technique was applied as a measuring instrument that consisted of 38 reagents with open, closed, dichotomous and multiple choice questions that allowed the perception of all teachers in the school. The obtained results indicate that the University has professionals in the areas of engineering with 44%, architecture with 10%, graduates in law representing 15%, while 24% are other professionals; which 73%, have an industry work experience in the field of study. On the other hand, they recognize that 95% have received some course of the teaching-learning process, of which 51% took this course in this year, 34% 2 years ago, 10% mentioned that over 5 years ago.

El presente trabajo de investigación de tesis aborda el Capital Intelectual como parte de los activos intangibles que poseen las personas que laboran en las empresas y es relevante para darle un valor económico. Las universidades en conjunto con sus colaboradores adquieren y generan conocimiento, ya que continuamente se presentan cambios tanto tecnológicos, científicos, así como nuevos procedimientos, entre otros. Los cambios son tan constantes que las empresas deben estar preparadas para recibirlos, sistematizarlos, aplicarlos y renovarlos. Sin embargo, es el Capital Intelectual el responsable de identificarlos, registrarlos, sistematizarlos y aplicarlos. Se efectúa la aplicación del Modelo Intelect de Euroforum en la Universidad Tecnológica de la Construcción, en la Ciudad de Morelia, Michoacán. Mediante el cual se abordan variables cuantitativas y cualitativas fundamentales en este constructo, facilitando evaluación del Capital Intelectual del personal docente. Buscando como único fin optimizar los recursos como parte integral de una estrategia que genere ventajas competitivas. Para el levantamiento de datos se aplicó la técnica del cuestionario como instrumento de medición que constó de 38 reactivos con preguntas abiertas, cerradas, dicotómicas y de opción múltiple que permitió conocer la percepción todos los docentes del plantel. Los resultados obtenidos indican que la Universidad cuenta con profesionistas de las áreas de ingeniería con 44%, arquitectura con un 10%, licenciados en derecho representan 15%, mientras que un 24% son otros profesionistas; los cuales 73%, cuentan con experiencia laboral en la industria del campo de su estudio. Por otra parte, reconocen que el 95% han recibido algún curso del proceso enseñanza-aprendizaje, de los cuales 51% recibió dicho curso en este año, 34% hace 2 años, 10% mencionó que hace más de 5 años.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2020-0213; Capital intelectual; Conocimiento; Modelo de medición; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6193